A mathematical model for flame volume estimation based on flame height of turbulent gaseous fuel jet. (October 2015) - Zhang, Xiaolei; Hu, Longhua; Wang, Qiang; Zhang, Xiaochun; Gao, Peng
Highlights: Mathematical model for flame volume estimation based on flame height proposed. Flame shape of turbulent gaseous fuel jets obtained experimentally. Unique data revealed for a sub-atmospheric pressure. Abstract: This paper investigates the flame shape and flame volume of turbulent gaseous fuel jets. Experiments are conducted for turbulent gaseous fuel jet flames produced by nozzles with different diameters of 4, 5, 6 and 8 mm using propane as fuel in both normal-(Hefei city: 100 kPa) and a sub-atmospheric pressure (Lhasa city: 64 kPa). The predicted flame shape outlines by the classic Baron's model are compared with the experimental results obtained by the Orloff's image analysis method. It is shown that Baron's method can well predict the width as well as the shape of the flame, although the predicted flame widths are slightly larger than the experimental results at the bottom and top part of the flame. Then, a mathematical model for the flame volume estimation is deduced by the integration of the Baron's expression, to provide an explicit and easily applied model to calculate the flame volume based on just the flame height. The proposed model is shown to fairly well predict the flame volume in both pressures although the predictions are a bit larger than the experimental values.